Optimal Regulatory Areas for Securities Disclosure - Merritt B. Fox (Washington University Law Quarterly, 2003)
The corporate governance scandals of 2003 have brought renewed focus on mandatory disclosure. One of the most fundamental questions relating to this kind of regulation is the choice of regulatory area. This Article constructs an economic-efficiency based theory of optimal regulatory areas for securities disclosure. While larger political and constitutional considerations unrelated to efficiency will inevitably also play a role in the resolution of the debates recounted above, efficiency considerations are important because they go to the capacity of capital markets to promote the generation of real wealth. The theory developed here can help identify the efficiency-related tradeoffs involved in choosing one level of government versus another and the information that is needed to choose intelligently. The primary focus of this Article is the proper level of government needed to regulate securities disclosure in a world with a high degree of international capital mobility. Part I briefly reviews the role of issuer disclosure in promoting economic efficiency and demonstrates that each issuer has a socially optimal level of disclosure. Part II identifies a regulatory structure for disclosure by the world’s issuers as having two components: a division of the world into a set of areas and a rule of territorial tie that assigns issuers to these different areas for regulation by their respective governmental units. Part III considers an ideal world conforming to assumptions that permit its division into geographic areas where there is very little economic integration across territorial lines except portfolio investment capital flows. Part IV considers the implications of the real-world breakdown in the assumptions relating to each area that are used to construct Part III’s ideal world. Part V concludes the Article by sketching how the overall analysis can be applied to current debates.
Keywords: Financial disclosure; Securities industry – Law & amp; legislation; Law & amp; economics; Securities; Cost effectiveness; Corporate governance; Government regulations